The Middle East and North Africa and the Global Trend towards Multiple Citizenship - (:unkn) unknown (My University, 2020)
The scholarship on dual/multiple citizenship seems to unanimously agree that there is, at the global level, an inevitable trend towards the toleration of multiple citizenship. After proving reluctant to accept dual membership, so the argument goes, most of the modern states have gradually given up on pretending controlling multiple allegiance. Within this global trend, the Arab states have been identified as lagging behind due to various reasons, in particular because of the ethnic and patriarchal understanding of nationality and the democratic deficit in the region. Yet, with few notable exceptions, the Middle East and North Africa (MENA) has surprisingly received little scholarly attention in the growing research of dual citizenship, despite the importance of international and transnational population movement within and through the region. Based on the comprehensive collection and review of the existing legislation, recent reforms and current debates regarding multiple citizenship, this chapter focuses on the region in order to debunk teleological and normative approaches or culturalist and essentialist visions. It shows that, despite a general reluctance to naturalisation being one source of dual nationality, there is in the MENA a wide diversity of historical and national approaches and contradictory trends.
Keywords: African Research